A strategic analysis of collective urban transport in Spain using the Five Forces Model - Alba Gómez Ortega; M. Luisa Delgado Jalón; José Ángel Rivero Menéndez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
The transport sector in Spain is a branch of economic activity which is already of great importance according to its own invoicing, value added and occupation figures, in addition to its indirect economic effects. It has an additional strategic value for economic policy, since it constitutes a fundamental part of the cost of placing products on increasing markets in a competitive manner. The mobility and transportation of passengers in cities in turn plays an essential role in the economic and social activity. All of these reasons, in addition to the recent significant problems of sustainability which this priority sector is currently confronting in all aspects, justify an interest in a study which attempts to obtain a profile of this public service by using a strategic analysis through the application of the traditional Porter Five Forces Model. The application of this model will allow us to obtain a general strategic vision which, when combined with a maturity analysis, will provide a more in-depth knowledge of the object under study, that will serve as a basis for subsequent analyses of the collective urban public transport service.
Keywords: R40; R49; M49; 330; Strategic; Abell; Porter; Sector; Urban transport; Public service